The Influence of Product Design and Product Variation on Purchasing Decisions At Distro Kiddrock Arjawinangun - Prasetyo, Dino Sapta; Adzikri, Faqih Utsman; Firmansah, Geri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to find out how much influence product design and product variations have partially and simultaneously. This research is quantitative, using associative quantitative data methods. This research uses primary data, namely a questionnaire distributed to 50 Kiddorck Arjawinangun consumers using a non-probability sampling technique with incidental sampling. Quantitative data was analyzed using validity tests, reliability tests, classical assumption tests, regression analysis, and hypothesis tests processed using the IBM Statistics SPSS 26 application. The results of testing product design variables partially had a positive and significant effect on purchasing decisions with a significance value of 0.003 < 0.05 and the calculated t value > t table or 3.106 > 1.677. The partial product variation variable also has a positive and significant effect on purchasing decisions with a significance value of 0.013 < 0.05 and a calculated t value > t table or 2.575 > 1.677. Simultaneously, product design variables and product variations have an influence of 41.8% on purchasing decisions. This is shown by the calculated F value of 18.584 which is greater than the F table of 3.191 and a significance value of 0.000 < 0.05.